Post-fire negative relationship between a native tree and an invasive pine at the Coastal Maulino Forest in Central Chile - Escobedo, Víctor M.; Gómez, Persy; Molina-Montenegro, Marco A.; Acuña-Rodríguez, Ian S. (Frontiers in Ecology and Evolution, 2024)
Coastal Maulino Forest, a biodiversity hotspot, is increasingly threatened by frequent and higher-severity wildfires. Endangered tree species, including Nothofagus spp., inhabit small, isolated native forest fragments surrounded by extensive Pinus radiata plantations, a non-native species that often colonises fire-affected areas. However, the seedling density of the native Chilean wineberry, Aristotelia chilensis, negatively correlates with the abundance of P. radiata seedlings in post-fire areas. This pattern emerged across areas burned at varying fire severities, sampled 8 and 24 months following the 2017 “Las Máquinas” megafire in Chile. The high proportion of plots lacking P. radiata seedlings, coupled with this negative relationship, suggests that A. chilensis may play a role in limiting P. radiata invasion. The negative relationship was most pronounced in areas with moderate fire severity, likely reflecting differences in shade tolerance between the species. While A. chilensis, a light-demanding species with some shade tolerance, can persist in partially shaded environments, P. radiata, a strictly light-demanding species, struggles under significant shade. In low-severity areas, no significant relationship was observed since the substantial native canopy remaining likely limits P. radiata establishment by shading. Conversely, in high-severity fire areas, the absence of a significant relationship might result from the detrimental effects on both species, including potential microbiome dependence for A. chilensis. Given the successful establishment of A. chilensis at low fire severity, enhancing its post-fire recruitment, particularly in moderately burned areas, could be a valuable strategy for mitigating P. radiata invasion and restoring fire-affected Mediterranean ecosystems.